Kualitas Hidup Ekuivalen Dengan Kualitas Sholat - syamsuddin kade; St. Johariah (Universitas Muslim Indonesia, 2022)
One indication that shows the primacy and position of prayer in Islam is that prayer is very important in the life of a Muslim. Even between prayer and life are one and inseparable. Prayer is a picture of life experienced by humans with various patterns and colors as well as situations and conditions which of course affect the mood of the soul. Prayer movements that go up and down the situational situation experienced by a Muslim who changes, some are happy, some are sad, even scary, worrying and others. Such is the reality of life. At the same time reading and prayer movements also teach a Muslim how to face life with its various trials. Prayer forms the character of sincerity, obedience, gratitude, istiqamah, patience, optimism, empathy for others, maintaining togetherness and integrity. Therefore, the quality of life of a Muslim is influenced by the ability to understand and explore every movement and reading of prayer and in the end the prayers performed have an impact on the actions that are not contrary to religious values and even provide many benefits in life. This proves that the quality of life of a Muslim is equivalent to the quality of prayer